Implementasi Kurikulum Sekolah Berwawasan Lingkungan Dalam Meningkatkan Rasa Peduli Lingkungan SMA N 2 Bantul - Fairuzzabadi Amrullah; Heru Nurcahyo (Universitas Negeri Padang, 2023)
The development and advancement of technology, human activities and behavior are not a few that have a bad impact on the environment due to the pollution produced. The concern of the educational environment is characterized by a specific environmental attitude made based on value-based theories. In the sense of environmental care for many environmental damages caused by human activities so that the surrounding environment becomes polluted and increases natural damage, this study aims to instill and increase a sense of environmental care starting from activities in schools, where schools are the initial place of an education to instill a sense of care for the environment. The method used in this study uses purposive sampling techniques with descriptive quantitative analysis techniques using interview, observation and document methods where the three methods are used complementary and equally strong in this study. The results of research that have been carried out by researchers at SMA 2 Bantul get very fulfilling results, where SMA N 2 Bantul obtained a final score of 96.49. On average, the school has supported an environmentally sound school curriculum, and has been used in the learning process, as well as the participation of school residents who maintain the school environment, and there is an interest from the school community in motivating themselves so that others are willing to do the same so that the school can achieve the goals of an environmentally sound and sustainable school.